Hypolipidemic Effect and Antioxidant Activity of Tamarind Leaves Extract in Hypercholesterol-Fed Rats - Aprilia, Citra Ayu; Ninditasari, Ghina; BR, Djoko Walujo (The Indonesian Heart Association, 2017)
Background: Higher cost and side effects made of some anticholesterol drugs usedin long time are the reasons why some people change to herbal therapies. Tamarind(Tamarindus indica) leaves is one of the herbal therapies. This research aims to determinehypolipidemic effect and antioxidant activity of extract of tamarind leaves (ETL).Methods: We used 25 rats as samples, divided into five groups of negative control(CMC 0.5%), positive control (Ezetimibe 1.26 g/kgBW)), first, second and third doseof ETL consequently are 0.93, 1.86 and 3.73 g/kgBW.Results: Paired-samples T-test showed ETL significantly decreased total cholesterol(TC), triglyceride (TG) level, and high-density lipoprotein cholesterol (HDL-C) levelsignificantly increased compared with negative control groups (p≤0.05). Low-densitylipoprotein cholesterol (LDL-C) level had significant difference only at second dose ofETL (p<0.05). Furthermore, the data’s difference between pre- and post-interventionwere analyzed with one-way ANOVA test in TC, TG, and HDL-C level, ETL had asignificant difference (p≤0.05), while there was no significant difference in LDL -Cbetween groups (p>0.05). Data were also analyzed by Post Hoc test. TC, TG, andHDL-C level had a significant difference between all variance ETL’s doses and positivecontrol compared with negative control group (p≤0.05). For antioxidant activity, ETLexhibited the significant reduction in the levels of malondialdehyde (MDA) by pairedsamplesT-test (p≤0.05) but there was no significant difference in both of MDA andsuperoxide dismutase (SOD) level (p>0.05) analyzed by One-way ANO VA test.Conclusion: All variant of ETL’s doses have hypolipidemic effect and antioxidant activity.ETL also has similar effect with Ezetimibe. Saponin, flavonoid, epicatechin, tanin, andpolyphenol that is contained likely contribute to these pharmacologic effects.